2016
DOI: 10.1007/s11433-015-5775-3
|View full text |Cite
|
Sign up to set email alerts
|

Helium-3 production from Pb+Pb collisions at SPS energies with the UrQMD model and the traditional coalescence afterburner

Abstract: A potential version of the UrQMD (UrQMD/M) transport model and a traditional coalescence model are combined to calculate the production of 3 He fragments in central Pb+Pb collisions at SPS energies 20-80 GeV/nucleon. It is found that the Lorentz transformation in the afterburner influences visibly the 3 He yield and should be considered in calculations. The rapidity distribution of 3 He multiplicities (including the concave shape) can be described well with UrQMD/M when it stops during t cut =100±25 fm/c and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…If we select two parameter sets of (R 0 , P 0 ), (3.5 fm, 0.3 GeV/c) and (3.8 fm, 0.3 GeV/c), which can both describe data well, it is found that the stopping times should be at 70 and 90 fm/c, respectively. This phenomenon was also seen in the previous work [17] even for higher SPS energies.…”
Section: The Urqmd and The Coalescence Model Settingssupporting
confidence: 88%
See 2 more Smart Citations
“…If we select two parameter sets of (R 0 , P 0 ), (3.5 fm, 0.3 GeV/c) and (3.8 fm, 0.3 GeV/c), which can both describe data well, it is found that the stopping times should be at 70 and 90 fm/c, respectively. This phenomenon was also seen in the previous work [17] even for higher SPS energies.…”
Section: The Urqmd and The Coalescence Model Settingssupporting
confidence: 88%
“…As a matter of experience, the values for the parameter set (R 0 , P 0 ) might be chosen in the range of (3-4 fm, 0.25-0.35 GeV/c) in order to describe experimental data from HICs at SIS, AGS, and even SPS energies. Within such a large beam energy region, the relativistic effect on δr and δp between two baryons have been taken into account by the well-known Lorentz transformation (LT) from the computational two-nucleus center-of-mass system to the local rest frame of two particles [16,17], and it is found that it has visible effect on light fragments, although not on free nucleons, which should be paid attention.…”
Section: The Urqmd and The Coalescence Model Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…对UrQMD模型的平均场、 碰撞项等部分做了相应 的改进 [26][27][28][29][30][31][32][33][34][35][36] . 当前版本进一步引入了Skyrme能量密 度泛函给出的表面能项、表面不对称项以及对称能 项:…”
Section: 末态粒子动量空间方位角分布进行傅里叶展开 即 Dnunclassified
“…The study of strongly interacting matter at extreme temperatures and densities is provided a chance by heavy ion collisions at ultrarelativistic energies [1][2][3][4][5]. The production mechanism of nuclei in ultrarelativistic heavy ion collisions deserves more investigation since it may give important message on the quantum chromodynamics (QCD) phase transition from quark-gluon plasma (QGP) to hadron gas (HG) [6,7]. The RHIC is scheduled to run at the energies which are around the critical energy of phase transition from hadronic matter to QGP [8].…”
Section: Introductionmentioning
confidence: 99%